Implementation of Electronic Signatures on Financial Administration Documents (A Study at the Regional Finance and Assets Agency of North Minahasa Regency) - De Breving, Novilya Shintya Netty; Kairupan, Sisca Beatrix; Tarore, Steven (Technium Social Sciences Journal, 2025)
This study aims to analyze the implementation of Electronic Signature (TTE) on financial administration documents at the Regional Finance and Assets Agency of North Minahasa Regency. The main focus of the research is directed at two important aspects, namely communication and socialization, which determine the success of TTE implementation in the local government bureaucracy. This research used a descriptive qualitative approach with data collection techniques through in-depth interviews, observation, and documentation on 5 key informants. The results showed that the implementation of TTE still faces various challenges that are quite complex. From the communication aspect, it was found that the lack of uniformity of understanding among employees was caused by unsystematic internal communication, informal delivery of instructions, and the absence of an official communication media specifically dealing with technical issues and policies related to TTE. In terms of socialization, the activities that have been implemented have not reached all employees evenly, are one-way, and are not equipped with supporting learning media such as written guidelines and video tutorials. In addition, there is no post-socialization technical assistance system in place, which has led to employees' dependence on colleagues who understand technology better. Other obstacles are also found in the aspect of human resources, such as limited employee competence in using TTE, lack of practical training, not optimal supporting infrastructure, and ineffective coordination between units and with external parties. Based on these findings, it is recommended to strengthen the internal communication system, improve the quality and scope of socialization, provide self-learning media, and form a technical team that can assist the TTE implementation process on an ongoing basis. Effective implementation is expected to encourage the creation of modern, transparent, and accountable financial administration governance.